What Should We Do with Our Depressions? Feelings, Biology, Politics - Renata Prati (Lateral)
The aim of this contribution is to explore some of the ways in which cultural studies, and more specifically affect studies and feminist new materialisms, have dealt with the problem of depression. My main argument is that, through these approaches and discussions, depression becomes a powerful site to delve into crucial controversies within affect theory and new materialisms, such as the distinction between affect and emotions and the related dichotomy between biology and culture, or the proper place of critique in contemporary thought. One glaring entry point to these controversies is the topic of antidepressants. In the 1990s, the so-called Decade of the Brain, a new generation of antidepressants took hold of the public imagination in the United States: the selective serotonin reuptake inhibitors, SSRIs, with Prozac (fluoxetine) on top. The 1990s also witnessed the emergence of both affect theory and new materialisms, and with them the shaping of some deep and enduring controversies. Indeed, almost twenty years later, these entangled debates were reenacted in two books: Ann Cvetkovich’s Depression: A Public Feeling (2012), originally prompted as a critical response to depression memoirs, and Elizabeth A. Wilson’s Gut Feminism (2015), strongly critical of what she considers to be the usual critique of antidepressants in cultural studies. Are antidepressants taking us closer to the true psychosomatic nature of bad feelings, or are they an insidious form of biopower? How should cultural studies, feminist, and queer work approach them? What do they say about depression and negative feelings in general? Are our feelings of distress mainly visceral and biological, or are they socially and culturally determined, or both? And how? How do the 1990s and 2010s controversies live on today?